Morphological variations and sex expression in gametophytes of Cibotium barometz under in vitro conditions - TITIEN NGATINEM PRAPTOSUWIRYO; YUPI ISNAINI (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. PraptosuwiryoTNg, Isnaini Y. 2017. Morphological variations and sex expression in gametophytes of Cibotium barometz under in vitro conditions. Biodiversitas 18: 312-320. Characteristics of gametophytes in ferns have been shown to be phylogenetically significant. Studies of fern gametophytes have become essential to fill the gaps in our knowledge of fern morphology, ecology, reproduction, evolution and distribution. The purposes of this study were: (i) to observe morphological variations and sex expression in gametophytes of Cibotium barometz (L.) J. Sm., and (ii) to understand how gametophyte densities affect sex expression in the species. Spores of five collection numbers of C. barometz from Sumatra, Indonesia, were sown on half-strength Murashige & Skoog (Â½MS) basal medium. Eleven weeks after germination of spores, prothalli were subcultured on Â½MS medium along with sugar (30 g/L) and Naphthalene Acetic Acid (NAA, 0.5 mg/L). After eight months subculturing of prothalli (prothallus density: 100-150 individuals per cm2), 100 gametophytes were observed for each collection number to determine their shapes and sex expression. Between 9- 12 months after subculturing, gametophytes growing at different population densities (between 100-500 individuals per cm2) were sampled. One hundred prothalli were selected among the ten replicates for each collection number. The percentage of each identified gametophyte shape and their genders were recorded. Eight morphological types of adult gametophyte were recorded: (i) Branching filament (asexual), (ii) ribbon-like shape (male), (iii) spatulate shape (asexual, male, female), (iv) heart shape (male, female, bisexual), (v) gemmiferous heart shape (asexual, female, bisexual), (vi) long heart shape (male, bisexual); (vii) gemmiferous long heart shape (asexual, male, bisexual), and (viii) gemmiferous irregular shape (asexual, male, female, bisexual). We conclude that gametophyte morphology is simply â€œtoo plasticâ€ to be used in suporting species delimitation in ferns if the prothalli is to be cultured in a high population density. There is a correlation between gametophyte size, shape and sex expression that is related to the population density. The presence of unisexual and bisexual gametophytes indicates that both intergametophytic and intragametophytic selfing occur in C. barometz. Keywords: Cibotium barometz, Environmental Sex Determination theory, gametophyte, morphology, sex expression